Health technology assessment frameworks for eHealth: A systematic review - Vis, Christiaan; Bührmann, Leah; Riper, Heleen; Ossebaard, Hans C. (International Journal of Technology Assessment in Health Care, 2020)
Traditionally, health technology assessment (HTA) focuses on assessing the impact of pharmaceutical technologies on health and care. Resources are scarce and policy makers aim to achieve effective, accessible health care. eHealth innovations are increasingly more integrated in all healthcare domains. However, how eHealth is assessed prior to its implementation in care practices is unclear. To support evidence-informed policy making, this study aimed to identify frameworks and methods for assessing eHealth's impact on health care. The scientific literature in five bibliographical databases was systematically reviewed. Articles were included if the study was conducted in a clinical setting, used an HTA framework and assessed an eHealth service. A systematic qualitative narrative approach was applied for analysis and reporting. Twenty-one HTA frameworks were identified in twenty-three articles. All frameworks addressed outcomes related to the technical performance and functionalities of eHealth service under assessment. The majority also addressed costs (n = 19), clinical outcomes (n = 14), organizational (n = 15) and system level aspects (n = 13). Most frameworks can be classified as dimensional (n = 13), followed by staged (n = 3), hybrid (n = 3), and business modeling frameworks (n = 2). Six frameworks specified assessment outcomes and methods. HTA frameworks are available for a-priori impact assessment of eHealth services. The frameworks vary in assessment outcomes, methods, and specificity. Demonstrated applicability in practice is limited. Recommendations include standardization of: (i) reporting characteristics of eHealth services, and (ii) specifying assessment outcomes and methods following a stepped-approach tailored to the functional characteristics of eHealth services. Standardization might improve the quality and comparability of eHTA assessments.